Habitat and History Influence Abundance of Bog Turtles. Issue 2 (27th November 2019) - Stratmann, Theresa S. M.; Floyd, Thomas M.; Barrett, Kyle
Abstract : Occupancy patterns of bog turtles in Georgia and South Carolina, USA, 2011–2014, were weakly related to percent of the wetland that was covered in emergent vegetation, and abundance patterns were predicted by the percent silt in the wetland substrate, percent forest cover, and past habitat degradation. These relationships reaffirm the need for habitat management that maintains open‐canopied wetlands and highlights that current population trends may not reflect current habitat status. ABSTRACT: Conservation of rare and endangered species requires assessment of factors that influence the current habitat associations of a species and the role of past habitat degradation in limiting occupancy or abundance. The objective of our 2011–2014 study was to determine how habitat characteristics and wetland history can predict occupancy and abundance patterns of bog turtles ( Glyptemys muhlenbergii ) at the fringe of their range in the southeastern United States. We used a hurdle model to examine occupancy and abundance patterns while addressing problems associated with zero‐inflated data. Occupancy patterns were weakly related to percent of the wetland containing emergent vegetation, whereas abundance patterns were predicted by the percent silt in the wetland substrate, percent forest cover, amount of habitat degradation, and recovery time since past habitat degradation. The effect of historical habitat degradation on abundance rather than occupancy patterns has rarely been documented and its effect is rarely studied in vertebrate populations. Identification of predictors of occupancy and abundance patterns will aid discovery of new populations of bog turtles and improve management of occupied wetlands. © 2019 The Wildlife Society.